The international primary ciliary dyskinesia cohort (iPCD Cohort): methods and first results. Issue 1 (5th January 2017) - Goutaki, Myrofora; Maurer, Elisabeth; Halbeisen, Florian S.; Amirav, Israel; Barbato, Angelo; Behan, Laura; Boon, Mieke; Casaulta, Carmen; Clement, Annick; Crowley, Suzanne; Haarman, Eric; Hogg, Claire; et al.
Data on primary ciliary dyskinesia (PCD) epidemiology is scarce and published studies are characterised by low numbers. In the framework of the European Union project BESTCILIA we aimed to combine all available datasets in a retrospective international PCD cohort (iPCD Cohort). We identified eligible datasets by performing a systematic review of published studies containing clinical information on PCD, and by contacting members of past and current European Respiratory Society Task Forces on PCD. We compared the contents of the datasets, clarified definitions and pooled them in a standardised format. As of April 2016 the iPCD Cohort includes data on 3013 patients from 18 countries. It includes data on diagnostic evaluations, symptoms, lung function, growth and treatments. Longitudinal data are currently available for 542 patients. The extent of clinical details per patient varies between centres. More than 50% of patients have a definite PCD diagnosis based on recent guidelines. Children aged 10–19 years are the largest age group, followed by younger children (≤9 years) and young adults (20–29 years). This is the largest observational PCD dataset available to date. It will allow us to answer pertinent questions on clinical phenotype, disease severity, prognosis and effect of treatments, and to investigate genotype–phenotype correlations. The iPCD Cohort offers a unique opportunity to study PCD in an international retrospective cohort of >3000 patients http://ow.ly/rn0m304Jgsu